NEW MAASTRICHTIAN OXYGEN AND CARBON ISOTOPE RECORD: ADDITIONAL EVIDENCE FOR WARM LOW LATITUDES - Zakharov Y.D.; Popov A.M.; Smyshlyaeva O.P.; Velivetskaya T.A.; Afanasyeva T.B.; Shigeta Y.; Sokolova E.A.; Nagendra R. (My University, 2006)
The Cretaceous period was generally characterized by greenhouse conditions. Nevertheless, our data on isotopic composition of biogenic carbonates from the Koryak Upland and Sakhalin (Russian Far East) show that during the Maastrichtian, temperatures dropped sharply at high and middle latitudes, with only a slight warming in the early Late Maastrichtian. At the same time, there is contradictory evidence on climatic conditions for low latitude areas during Maastrichtian time. The new and previously published isotopic data on Maastrichtian mollusks in the Western Interior Seaway (North America) (WIS) and some other areas suggest that tropical deep-sea surface temperatures calculated from the oxygen isotopic composition of the majority of investigated Maastrichtian planktic foraminifera are, obviously, underestimated. Unusually low isotopic temperatures were obtained for tropical planktic foraminifera. This probably reflects both local conditions provoked, first of all, by the influence of tropical upwelling zones, and the ability of Maastrichtian planktic foraminifera to migrate within a large vertical interval in the tropical zone in conditions of weakly stratified (well-mixed) ocean. The average tropical deep-sea surface paleotemperature estimates for the Maastrichtian could have been about 26.6-30.2°C, but, apparently, did not reach the level denoted for the Late Albian and Turonian (32±3°C). Negative carbon-isotopic shifts at the end of the early Maastrichtian and the Cretaceous-Tertiary boundary time seem to be connected with the fall of temperature and eventual reduction of oxygen content in the atmosphere and hydrosphere.
Keywords: CARBON-ISOTOPIC ANOMALIES; INVERTEBRATES; ISOTOPIC PALEOTEMPERATURES; MAASTRICHTIAN; PACIFIC AND ATLANTIC OCEANS; Mesozoic::Cretaceous::Upper::Maastrichtian; Мезозой::Меловая::Верхний::Маастрихтский